Genome-wide identification, characterization and expression analysis of CNGC Genes in moso bamboo (Phyllostachys edulis) - Jiaqi Tan; Xueyun Xuan; Shiying Su; Hui Guo; Yang Jiao; Zhijun Zhang (BMC Plant Biology)
Abstract Background The CNGC gene family, which belongs to a group of non-selective cation channels responsible for the regulation of crucial cations such as Ca2+, K+, and Na+, assumes a pivotal function in diverse physiological and biochemical mechanisms, including plant development, growth, signal transduction, and response to abiotic stresses. While the CNGC gene family has been extensively explored in model plants, its functional study in moso bamboo (Phyllostachys edulis) has not yet been established. Results In this investigation, an extensive breakdown of the CNGC gene family in moso bamboo was conducted, resulting in the identification of a total of 25 CNGC genes, which were found to be irregularly distributed across 12 chromosomes. As analyzed from the phylogenetic tree, the CNGC gene family in moso bamboo could be categorized into four distinct classes. Family members of this gene exhibited minimal variations in terms of gene structures, conserved motifs, and distribution of structural domains. Multiple cis-elements involved in positive regulation were present in the ascending promoter domain of the CNGC gene sequence, with a role in abiotic stress and hormone signal transduction. Plenty of fragment repetitive events have been identified in the CNGC gene family, driving gene amplification. Moreover, both STEM timing expression analysis and qRT-PCR confirmed a close association between PeCNGC and the speedy growth of bamboo shoots. Subcellular localization experiments demonstrated the presence of PeCNGC in the cell membrane, while protein structure analysis classified it as a typical membrane protein with an ion-transport channel. Genetic complementation experiments conducted in yeast deletion mutants provided further evidence supporting the direct involvement of PeCNGC in potassium ion transport. Conclusions We selected moso bamboo as the experimental subject for the first time and performed bioinformatics analysis and expression characteristics analysis of the CNGC gene family. This research set the stage for future comprehensive examinations of the function of the CNGC gene family and the molecular breeding mechanisms that contribute to the speedy growth of moso bamboo shoots.